2023
DOI: 10.1161/jaha.122.029130
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Characteristics of Individuals With Fontan Circulation With Blood and Urine Biomarkers of Kidney Injury and Dysfunction

Abstract: Background Fontan circulation is associated with kidney injury and dysfunction, often unappreciated until Fontan circulatory failure. We hypothesized that cystatin C‐estimated glomerular filtration rate (eGFR) would identify chronic kidney disease more frequently and that urine kidney injury biomarkers would be higher with declining Fontan physiological features. Methods and Results We enrolled 100 ambulatory individuals. Blood and urinar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Furthermore, the CKD‐EPI40 does not rely on height, which is often smaller given somatic growth restriction and incomplete catch‐up growth in patients with a Fontan circulation. 27 This enhancement in accuracy is illustrated through comparison with a recent study by Katz et al, 28 wherein the bedside Schwartz equation identified reduced kidney function in a mere 11% of patients with a Fontan circulation. In contrast, our present study, despite dealing with a marginally younger cohort (median age, 16 years versus 19 years), identified twice the number of affected patients, underscoring the tangible advantages of embracing the CKD‐EPI40 equation.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Furthermore, the CKD‐EPI40 does not rely on height, which is often smaller given somatic growth restriction and incomplete catch‐up growth in patients with a Fontan circulation. 27 This enhancement in accuracy is illustrated through comparison with a recent study by Katz et al, 28 wherein the bedside Schwartz equation identified reduced kidney function in a mere 11% of patients with a Fontan circulation. In contrast, our present study, despite dealing with a marginally younger cohort (median age, 16 years versus 19 years), identified twice the number of affected patients, underscoring the tangible advantages of embracing the CKD‐EPI40 equation.…”
Section: Discussionmentioning
confidence: 85%
“… 31 Imprecision of eGFR measurements, as expressed as the IQR of the difference between measurements, is 15.4 (IQR, 14.3–16.5) mL/min per 1.73 m 2 and can also lead to discordant results between eGFR and mGFR as has commonly been reported in the literature. Furthermore, it has been suggested that creatinine‐based eGFR methods would overestimate mGFR in patients with a Fontan circulation because of its reliance on skeletal muscle mass, 28 , 29 which is known to be reduced in these patients. 32 Cystatin C–based methods have been proposed to circumvent this issue; however, the applicable equations designed for the pediatric and adolescent demographic only became available after our study's enrollment phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Fontan circulation is associated with kidney injury and dysfunction, often unappreciated until Fontan circulatory failure. 5 It hypothesized that cystatin C-estimated glomerular filtration rate (eGFR) would identify chronic kidney disease more frequently and that urine kidney injury biomarkers would be higher with declining Fontan physiological features. 5 Cystatin C levels were associated with disease severity and prognosis in patients with pre-capillary PH.…”
Section: Introductionmentioning
confidence: 99%
“…5 It hypothesized that cystatin C-estimated glomerular filtration rate (eGFR) would identify chronic kidney disease more frequently and that urine kidney injury biomarkers would be higher with declining Fontan physiological features. 5 Cystatin C levels were associated with disease severity and prognosis in patients with pre-capillary PH. 6 A combination of high cystatin C and advanced WHO-FC identifies patients at particularly high risk of clinical deterioration.…”
Section: Introductionmentioning
confidence: 99%